MENINGKATKAN KEAKTIFAN DAN HASIL BELAJAR SISWA MELALUI MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) PADA SISWA KELAS 4 SD - Andika Dinar Pamungkas; Firosalia Kristin; Indri Anugraheni (NATURALISTIC : Jurnal Kajian Penelitian Pendidikan dan Pembelajaran, 2018)
The purpose of this study is to increase student activity and learning outcomes through the application of problem based learning learning models. This type of research is PTK. Subjects of grade IV students. Data collection techniques using tests, observation data, activeness assessment rubrics. Data analysis techniques used are quantitative and qualitative descriptive. The results of the activeness of learning activities in pre-cycle (64.87%) 24 students inactive in the first cycle increased to (24.32%) 9 students were quite active and in the second cycle increased to (83.78%) 31 students were active. Whereas for pre-cycle learning outcomes showed completeness of (41%) 15 students completed then increased in cycle 1 to (54%) 20 students completed and (81%) 30 students completed in cycle II. Thus the application of problem based learning learning models can improve the activeness and learning outcomes of fourth grade students of SDN Panjang 03.